Crosslinked cellulose thin film composite nanofiltration membranes with zero salt rejection - Puspasari, Tiara; Pradeep, Neelakanda; Peinemann, Klaus-Viktor (Journal of membrane science, 2015)
We report a new synthetic route of fabricating regenerated cellulose nanofiltration membranes. The membranes are composite membranes with a thin selective layer of cellulose, which was prepared by regeneration of trimethylsilyl cellulose (a hydrophobic cellulose derivative) film followed by crosslinking. Filtration experiments using mixtures of sugar and sodium chloride showed that solutes above 300Da were highly rejected whereas practically no rejection was observed for NaCl. This is a big advantage for a complete desalination as the existing commercial nanofiltration membranes typically exhibit NaCl rejection in the range of 30–60%. Membranes with zero NaCl rejection are required for recovery and purification applications in food, chemical and pharmaceutical industry. [Display omitted] •Thin-film cellulose composite nanofiltration membranes are prepared.•NF-membranes with 300Da MWCO and zero salt rejection.•Silylated cellulose as precursor for thin crosslinked cellulose films.